Approximation of fractional-order integrals by algebraic polynomials. II - Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the approximation of functions that are fractional-order integrals of bounded functions by algebraic polynomials.